We need to refer to the mathematical definition of the word "even."
The most commonly accepted definition is that a number "a" is even if there exists an integer "n" which makes the following statement true:
a = 2 x n
-1 is an integer. So let n = -1 in the above equation and we get:
-2= 2 x (-1)
So -2 satisfies the mathematical definition for being even.
Chat with our AI personalities
This is not always true. If the sum of two numbers is even, then those two numbers are either both even or both odd. For example: 2 + 2 = 4 (even + even = even) 5 + 7 = 12 (odd + odd = even) 3 + 2 = 5 (odd + even = odd)
If the sum of two numbers is even, the two numbers are either both even or both odd. A few examples:2 + 4 = 6 (even + even = even)2 + 3 = 5 (even + odd = odd)5 + 2 = 7 (odd + even = odd)7+13 = 20 (odd + odd = even)
No -an odd and an odd equals even ( 5+3=8) -an even and an odd equals odd (2+3=5) -an even and an even equals even (4+6=10)
An even number can be divided by 2 evenly. An odd number will have a remainder of 1 when divided by 2. Even plus odd is odd.
0 is a number to divide the positives and the negitives. Then it will be an even in this timeline. -2, -1, 0, 1, 2 Because it goes even odd even odd even. If zero was not there, then it would go even odd odd even.